2020
DOI: 10.1002/bjs.11653
|View full text |Cite
|
Sign up to set email alerts
|

Axillary nodal metastatic burden in patients with breast cancer with clinically positive axillary nodes

Abstract: Background: The aim of this study was to determine preoperative factors and tumour characteristics related to a high nodal tumour burden in patients with clinically node-positive breast cancer. These findings were used to construct a predictive tool to evaluate the patient-specific risk of having more than two axillary lymph node metastases. Methods: Altogether, 507 consecutive patients with breast cancer and axillary lymph node metastasis diagnosed by preoperative ultrasound-guided needle biopsy were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Several factors suggest that patients from this database generally received correct management according to the standard of care ( 42 , 43 ), such as strong association of SLNBL with pN0, increased number of dissected LNs in those that received mastectomy ( 1 , 2 ), increased survival of luminal hybrid (HR + /HER2 + ) patients (not shown) as a function of the benefits of anti-HER2 therapy ( 44 – 46 ), and decreased survival of patients submitted to mastectomy/radical surgery (data not shown) ( 47 ). However, as already mentioned, no report of SLNB or clinical staging of the axilla is available in the SEER database ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors suggest that patients from this database generally received correct management according to the standard of care ( 42 , 43 ), such as strong association of SLNBL with pN0, increased number of dissected LNs in those that received mastectomy ( 1 , 2 ), increased survival of luminal hybrid (HR + /HER2 + ) patients (not shown) as a function of the benefits of anti-HER2 therapy ( 44 – 46 ), and decreased survival of patients submitted to mastectomy/radical surgery (data not shown) ( 47 ). However, as already mentioned, no report of SLNB or clinical staging of the axilla is available in the SEER database ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as already mentioned, no report of SLNB or clinical staging of the axilla is available in the SEER database ( 4 ). It is important to state that, although reduced for pT1–T2 patients, the clinical axillary staging is predictive of increased axillary burden ( 42 ), but the clinical staging is inferior and does not replace the pathological staging ( 43 ). More importantly, similar results in the matched analysis by propensity score between subsets of pN1 patients and pN2 patients, and those obtained of the prognostic value of affected to removed lymph node ratio in pN1, strengthen our conclusions that an intrinsic (basal) prognostic difference exists according to the number of resected lymph nodes by a probable downstaging.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach to nodal metastasis in breast cancer has undergone numerous evolutions with the aim of reducing morbidity and BCRL rates related to ALND. The advent of SLNB mitigated unnecessary ALND in clinically node-negative patients, and drastically reduced the rates of lymphedema in this group of patients [6]. The ACOSOG Z-0011 and EROTC AMAROS trials demonstrated that patients one or two metastatic sentinel nodes after SLNB, could safely avoid a completion ALND with the use of adjuvant radiotherapy [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, a normal lymph usually shows as a reniform shape, uniformly hypoechoic cortex with a maximal thickness less than 3 mm, smooth margins, and intact central fatty hilum [18]. On the contrary, suspicious ndings of ALN are cortical thickness greater than 2.5-3.0 mm, focal cortical lobulation, loss of the fatty hilum, a round shape, and abnormal cortical blood ow [19]. Kuna SK suggested that the short diameter of lymph nodes > 0.5 cm should be used as the index of judging the pathological lymph nodes, and especially when the short diameter > 1 cm, it should be suspected to be malignant [20].…”
Section: Discussionmentioning
confidence: 99%